Development and Validation of Performance Assessment Instrument in UV-Vis Spectrophotometry Practicum - Santika Santika; Firman H; Nahadi Nahadi (AIBPM Publisher, 2020)
Performance assessment in the instrument laboratory had been required to identify the students’ competency objectively. This research aimed to provide a performance assessment instrument in UV-Vis spectrophotometry practicum. The method was the development and validation through 4 stages: planning, development, validation, and evaluation. The validation results collected by the expert team described that among 17 valid assessments, the 14 were valued CVR 1, and the rest were invalid with value CVR 0.6 below the critical point (0.736). Meanwhile, the overall assessment validations were valid with value CVI 0.93. Based on questionnaires on several chemistry teacher instruments, they all agreed that performance assessment, which had been developed, was effective and feasible to use.